Freeze-Drying Ethylcellulose Microparticles Loaded with Etoposide for In Vitro Fast Dissolution and In Vitro Cytotoxicity against Cancer Cell Types, MCF-7 and Caco-2 - Ahmed A. H. Abdellatif; Mashari A. Aldhafeeri; Waleed H. Alharbi; Fahad H. Alharbi; Waleed Almutiri; Mohammed A. Amin; Mohammed F. Aldawsari; Hamzah M. Maswadeh (Applied Sciences, 2021)
The aim of this study was to improve the solubility of etoposide–ethylcellulose (ET–ETO) microparticles using the freeze-drying technique. Ethylcellulose (EC) microparticles loaded with etoposide (ETO) were prepared with different drug–polymer molar ratios of 1:1, 1:3, 1:6, and 1:20 by the solvent evaporation method. The size of the prepared microparticles was 0.088 µm. The results showed that the amount of ETO encapsulated into the microparticles was 387.3, 365.0, 350.0, and 250 µg/50 mg microparticles for microparticles with drug–polymer ratios of 1:1, 1:3, 1:6, and 1:20, respectively. The FT-IR spectra showed no chemical interaction between ETO and the polymer in the solid state. The results obtained from the dissolution experiment showed that the freeze-dried microparticles were stable in 0.1 N HCl (gastric pH) for 2 h. At pH 7.4, the ETO release was 60 to 70% within the first 15 min and approximately 100% within 30 min. Results from the application of different dissolution models showed that the equations that best fit the dissolution data for the ET–ETO microparticles at pH 7.4 were the Higuchi and Peppas model equations. The in vitro cytotoxicity assay of free ETO and freeze-dried microspheres prepared in this study with a drug–polymer ratio of 1:1 was performed in two mammalian cancer cell lines, MCF-7 (for bone cancer of the mammary organ) and Caco-2 (for mammalian epithelial colorectal adenocarcinoma). The results showed that the half-maximal inhibitory concentrations (IC50 values) for ETO and freeze-dried ET–ETO microparticles were 18.6 µM and 27.1 µM, respectively. In conclusion, freeze-dried ET–ETO is a promising formulation for developing a fast-dissolving form of ETO with a significant antiproliferative activity against the tested cell lines used in this study. It is a promising formulation for local duodenal area targeting.